PD-L1 Blockade by Atezolizumab Downregulates Signaling Pathways Associated with Tumor Growth, Metastasis, and Hypoxia in Human Triple Negative Breast Cancer - Reem Saleh (3513056) (2019)
Triple negative breast cancer (TNBC) is the most aggressive type of breast cancer, which shows resistance to common breast cancer therapies, as it lacks the expression of the most common breast cancer targets. Therefore, TNBC treatment remains a challenge. Targeting programmed cell death-ligand 1 (PD-L1) by monoclonal antibodies (mAbs), for example, atezolizumab, has revolutionized the treatment for various cancer types. However, the therapeutic efficacy of targeting PD-L1 in TNBC is currently under investigation. In this study, we investigated the molecular mechanisms by which the human TNBC cell line MDA-MB-231, expressing PD-L1, responds to atezolizumab, using RNA-Seq. Transcriptome analysis revealed 388 upregulated and 362 downregulated genes in response to atezolizumab treatment. The expression of selected genes, from RNA-Seq data, was subsequently validated using RT-qPCR in the MDA-MB-231 and MDA-MB-468 TNBC cells following atezolizumab treatment. Bioinformatics analysis revealed that atezolizumab downregulates genes promoting cell migration/invasion and metastasis, epithelial-mesenchymal transition (EMT), cell growth/proliferation/survival, and hypoxia. On the contrary, genes associated with apoptosis and DNA repair were upregulated in response to atezolizumab treatment. Gene set enrichment analyses revealed that a significant number of these genes are related to the NF-kB, PI3K/Akt/mTOR, MAPK, and CD40 signaling pathways. Using functional assays, we confirmed that atezolizumab increases MDA-MB-231 cell apoptosis/necrosis, and reduces their proliferation and viability. Collectively, our findings provide novel insights into the molecular mechanisms/signaling pathways by which atezolizumab exerts inhibitory effects on TNBC, thereby inhibiting EMT/metastasis, tumor growth/survival, and the induction of hypoxia. Other Information Published in: Cancers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/cancers11081050